Local treatment of HVJ-E with T cell costimulatory molecule stimulation elicits systemic anti-tumor effects - Airi Ishibashi; Yue Li; Yuuta Hisatomi; Noriko Ohta; Yuko Uegaki; Atsushi Tanemura; Riuko Ohashi; Koji Kitamura; Kotaro Saga; Yasuhide Yoshimura; Satoko Inubushi; Kyoso Ishida; et al. (Molecular Therapy: Oncology)
The tumor-infiltrating lymphocyte (TIL) is a crucial factor in controlling tumor growth. A therapeutic method activating TIL is desired for treating patients with metastatic tumors. Here, we show that treating a local tumor with a combination therapy of UV-irradiated hemagglutinating virus of Japan envelope (HVJ-E) plus agonist antibodies, including OX40, against T cell costimulatory molecules induces systemic anti-tumor effects in a T cell-dependent manner in multiple cancer cell lines. Transcriptome and T cell receptor repertoire analyses revealed that HVJ-E + anti-OX40 antibody treatment activates CD4 and CD8 T cells and promotes T cell trafficking between tumors. These systemic anti-tumor effects required an association between Nkg2d and Nkg2d ligands. Our findings provide insights into how systemic anti-tumor effects are induced and may help the development of therapeutic strategies for eliciting such effects.